Customer satisfaction with green initiatives in Malaysian hotels - Yusnita Yusof
Environmental issues are among the critical problems plaguing the world. Since the hotel industry is closely and directly related to the environment, hotels should take initiatives to reduce any negative impact on the environment. This study was conducted to examine customer perceptions of green initiatives; namely, concerning the green practices and the green image of a hotel, and how these impact their satisfaction and loyalty to the hotel. In this study, green practices and green image act as the independent variables, while customer loyalty acts as the dependent variable. Customer satisfaction has been identified as the mediating factor on the relationship of green practices and green image with customer loyalty. This study us d quantitative method and supported with qualitative method. For the quantitative method, questionnaires were distributed to respondents face-to-face. From th qu stionnaires collected, 300 respondents were selected using a random sampling meth d nd analyzed using SP S find AMOS. To strengthen and explore in depth the results obtained through this quantitative analy is the researchers collected data through qualitative methods by means of focus group discussions and interviews. A t tal of 11 respondents were involved in the focus group discussions, and three respondents were chosen t be interviewed. The results of the inference analysis, such as T -test and AN VA, showed that selected demographic factors, such as gender, age, race, education level, frequency of staying in the hotel, hotel star rating and citizenship, did not make a difference to the levels of customer loyalty to the hotel occupied. Ba ed n structural equation modeling, the study found that green image has a significant relationship with customer satisfaction and customer loyalty. In addition, customer satisfaction also acts as a mediator in the relationship between green image and customer loyalty. Although green practices have a significant relationship with customer satisfaction and customer loyalty, there is a negative relationship between green practices and customer satisfaction. Customer satisfaction also acts as a mediator in the relationship between green practices and customer loyalty. The results the focus group discussion and interviews show that nine factors lead to custome di atisfaction with hotels adopting green practices: customers' lack of awareness of environmental issues, low awareness of environmental problems among hoteliers, room price, customer attitude, hotel management being more focused on operati n and not ready to adopt green practices, facilities not comparable to the price paid and customer needs. Studies on customer needs when staying in hotels show that the issues of concern are cleanliness, comfort, facilities provided and quality commensurat with the room rates, security, user friendly website, attractive hotel environm nt, parking facilities, friendly employees, detailed information about green practices, accepting feedback from customers, food choice, brand reputation, reasonable price, Internet, easy payment, accessibility, and hospitality. The results of this study are useful to hotel management for identifying customer needs. Furthermore, hotel management can enhance and improve the services and products provided according to the green standards that have been established to reduce any negative impact on the environment.